Te mauri kōhatu : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy, The University of Massey, 2003 - McClintock, Kahu (Massey University, 2003)
This saying encapsulates the sentiments expressed within this thesis. The major mission of the study is to gather and preserve the tribal knowledge belonging to my iwi Ngāti Maniapoto, on Te Mauri Kōhatu. The assignment honours the understanding of the traditional beliefs and practices associated with the ancient lore of the Kōhatu. Anchoring the practice is the traditional notion that Te Mauri Kōhatu were a means to enhance health and wellbeing. This belief has existed for Māori since time immemorial. According to oral traditions the ancestor Tāne te Wānanga¹Te Hurinui (1959a) a Tainui, Ngāti Maniapoto scholar recorded that Tāwhaki secured three Kete ō te Wananga. However he made no mention of the accompanying Kōhatu that are important to this thesis. Other literary contributions by Te Hurinui (1959a, 1959b, 1962) are included in this thesis under the name Jones (1945, 1971, 1995). Another Tainui source National Library of New Zealand and Rangiātea (church) Te Rōpū Whakahaere and New Zealand Ministry of Māori Development (1997) documented that Tane te Wānanga received the three Kete ō te Wānanga and two accompanying Kōhatu. ascended into the Toi ō Ngā Rangi, the highest realm of the Rangitūhāhā. From there he secured the three Kete ō te Wānanga, the three Baskets of Knowledge. Accompanying this wisdom were two Mauri Kōhatu; the Whatukura ā Tāne and the Whatukura ā Tangaroa. Traditions also support the notion that from these two Kōhatu came the understanding of the spiritual and healing properties associated with Te Mauri Kōhatu. Articulated in the research is a significant body of wisdom gifted by my Ngāti Maniapoto elders to benefit the descendants of our iwi, both spiritually and intellectually. Ngāti Maniapoto ancestors arrived in Aotearoa / New Zealand on board the voyaging waka Tainui. The safe delivery and continued existence, of my ancestors in this land was credited to their belief in the power and the force of Te Mauri Kōhatu. The ancient lore of the Kōhatu guided their movements on both land and sea. Ngāti Maniapoto ancestors have, throughout the generations, perpetuated the ancient lore of the Kōhatu in our Ngāti Maniapoto tribal homelands. The writing of my thesis is an opportunity to gather, retain and celebrate our knowledge, our heritage that will advance the health and wellbeing of the descendants of Ngāti Maniapoto now and in times to come.
Keywords: Maori (New Zealand people); Medicine; Rites and ceremonies; Intellectual life; Ngāti Maniapoto (New Zealand people); Māori Master's Thesis